Synthesis and Characterization of Some New Ni, Cu and Co Complexes with Azo-Shciff Base Ligand - Mosa Jaafar Mosa (Journal of Global Pharma Technology, 2017)
Azo-schiff base lig and prepared by other obvious studies but we use special amine compound amino acid lysine, bath of azo and schiff base were characterized by FT-IR and H1NMR spectroscopy to notice the different resulting from condensation reaction [Co (AHDB)2] +2,[ Co (AHDB)2] +2 and [ Ni (AHDB)2] +2 complexes with a two molecules of bidentate ligand were synthesized  and identified by using various spectroscopic techniques. Obtained difference in UV-Vis spectrum between ligand and complexes indicates on successful of complication reaction appearance of band belong to d-d transition and didn’t found in ligand spectra, another indication of complication is the H1NMR spectrum show the same chemical shifts in both ligand and complexes cases with small shifting in ppm region which is expected result.Keywords: Azo-schiff base ligand, Cobalt tetra coordinate complexes, Amino acid schiff base.